2005
DOI: 10.1007/s00066-005-1452-1
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Three–Dimensional Analysis about the Impact of Differences in the Clinical Target Volume in Prostate Cancer Irradiation on Normal–Tissue Exposure

Abstract: Reduction of the CTV to the prostate only, or to the prostate + proximal seminal vesicles led to significant rectal and bladder dose sparing compared to irradiation of the prostate + entire seminal vesicles. In patients with a higher risk for seminal vesicles involvement, irradiation of the prostate + proximal seminal vesicles should be preferred. In case of a need for irradiation of the entire seminal vesicles, patients should be informed about a higher risk for chronic rectal toxicity and, possibly, for blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Similarly, the risk for rectal and bladder tumors is increased after radiotherapy for cervix cancer [17]. In these circumstances, a reduction of late effects, e.g., by more conformal treatments [16,19,21], may reduce the risk for second cancers.…”
Section: Induction and Manifestation Of Second Tumorsmentioning
confidence: 99%
“…Similarly, the risk for rectal and bladder tumors is increased after radiotherapy for cervix cancer [17]. In these circumstances, a reduction of late effects, e.g., by more conformal treatments [16,19,21], may reduce the risk for second cancers.…”
Section: Induction and Manifestation Of Second Tumorsmentioning
confidence: 99%
“…However, when such approach is applied, the volume of the irradiated normal structures must be reduced in order to limit normal tissue injury [5,9,12,14,15,18]. The main limitations in margin reduction are the setup errors and organ-motion (prostate motion due to rectum and bladder filling).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kestin et al [15] exposed that among patients presenting SV involvement after radical prostatectomy (all risk groups taken together), only 7% had an SV involvement beyond 1 cm and 1% beyond 2 cm. In order to reduce the rectal irradiated volume, the authors proposed to include, within the CTV, only the proximal (2-2.5 cm) part of the SV, especially for high-risk patients [27]; Hille et al confirmed those data [12].…”
Section: Discussionmentioning
confidence: 67%